How To Harvest the Anterolateral Thigh Free Flap - Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Triatmoko, Sara Ester; Ralena, Nadhira Anindita (Jurnal Plastik Rekonstruksi, 2020)
Summary: The anterolateral thigh (ALT) flap is the flap with various components based on perforators from the descending branch of the lateral circumflex femoral artery. This flap has a number of advantages and disadvantages. It can be used to reconstruct defects after oncologic resection and coverage following amputation or to preserve limb length. The contraindications include unsuitable donor sites, inadequately debrided recipient sites, and morbid obesity. Preparations for ALT procedure consist of history taking, physical examinations, and supporting examinations.